(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explains in detail about frustration, theories of frustration, S. Rosensweig’s theory of frustration, J. Dollor’s theory of frustration aggression, K. Lewin’s field theory and Z. Freud’s psychoanalytic theory.